Effects of digested Cheonggukjang on human microbiota assessed by in vitro fecal fermentation - Singh, Vineet; Hwang, Nakwon; Ko, Gwangpyo; Tatsuya, Unno (The journal of microbiology, 2021)
In vitro fecal fermentation is an assay that uses fecal microbes to ferment foods, the results of which can be used to evaluate the potential of prebiotic candidates. To date, there have been various protocols used for in vitro fecal fermentation-based assessments of food substances. In this study, we investigated how personal gut microbiota differences and external factors affect the results of in vitro fecal fermentation assays. We used Cheonggukjang (CGJ), a Korean traditional fermented soybean soup that is acknowledged as healthy functional diet. CGJ was digested in vitro using acids and enzymes, and then fermented with human feces anaerobically. After fecal fermentation, the microbiota was analyzed using MiSeq, and the amount of short chain fatty acids (SCFAs) were measured using GC-MS. Our results suggest that CGJ was effectively metabolized by fecal bacteria to produce SCFAs, and this process resulted in an increase in the abundance of Coprococcus, Ruminococcus , and Bifidobacterium and a reduction in the growth of Sutterella , an opportunistic pathogen. The metabolic activities predicted from the microbiota shifts indicated enhanced metabolism linked to methionine biosynthesis and depleted chondroitin sulfate degradation. Moreover, the amount of SCFAs and microbiota shifts varied depending on personal microbiota differences. Our findings also suggest that in vitro fecal fermentation of CGJ for longer durations may partially affect certain fecal microbes. Overall, the study discusses the usability of in vitro gastrointestinal digestion and fecal fermentation (GIDFF) to imitate the effects of diet-induced microbiome modulation and its impact on the host.